2012
DOI: 10.1007/978-3-642-30347-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Train Marshalling Is Fixed Parameter Tractable

Abstract: Abstract. The train marshalling problem is about reordering the cars of a train using as few auxiliary rails as possible. The problem is known to be NP-complete. We show that it is fixed parameter tractable (FPT) with the number of auxiliary rails as parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It has also be shown that the competitive factor of 2 is indeed best possible among all deterministic online algorithms. In [26], Brueggeman et al established that the TMP is fixed parameter tractable with respect to the number of classification tracks k. To be more precise, if an inbound train T with n railcars having t different arXiv:1903.08364v1 [cs.DS] 20 Mar 2019 c 2019 IEEE. Personal use of this material is permitted.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also be shown that the competitive factor of 2 is indeed best possible among all deterministic online algorithms. In [26], Brueggeman et al established that the TMP is fixed parameter tractable with respect to the number of classification tracks k. To be more precise, if an inbound train T with n railcars having t different arXiv:1903.08364v1 [cs.DS] 20 Mar 2019 c 2019 IEEE. Personal use of this material is permitted.…”
Section: Introductionmentioning
confidence: 99%
“…Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works. destinations, and a positive integer k are given, then for deciding whether or not the railcars of T can be rearranged in an appropriate order by using at most k classification tracks, the algorithm proposed in [26] requires O(2 O(k) poly(n)) time and O(n 2 k2 8k ) space. The algorithm is based on the dynamic programming (DP) paradigm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2000, Dahlhaus et al [6] proved that TMP is N P-complete and introduced new bounds. Brueggeman et al show in [7] that the problem is fixed parameter tractable. In another work by Dahlhaus, Manne, Miller and Ryan [8] they described similar problems.…”
Section: Introductionmentioning
confidence: 99%